1997
DOI: 10.1097/00007890-199703270-00011
|View full text |Cite
|
Sign up to set email alerts
|

Graft-Versus-Host Disease After Bone Marrow Transplantation for Thalassemia

Abstract: We analyzed risk factors in 724 patients evaluable for acute graft-versus-host disease (GVHD) and in 614 patients evaluable for chronic GVHD who had received bone marrow transplantation (BMT) from HLA-identical siblings and/or parents for thalassemia and/or microdrepanocytosis, in a single institution. The overall incidence of grade II-IV and III-IV acute GVHD (aGVHD) was 26.9% and 13.5%, respectively. The cumulative incidence of grade II-IV aGVHD in patients treated with cyclosporine (CsA)/methylprednisolone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 31 publications
2
49
0
1
Order By: Relevance
“…We have previously reported 17% of grade 2-4 aGVHD following CSA/MP/MTX (CY on day þ 1) prophylaxis in class 3 adult and pediatric patients. 3 However, it should be acknowledged that most patients in that study had early graft failure (up to 30%) and a competing risk analysis was not performed to calculate the cumulative incidence of aGVHD. Therefore, the cumulative incidence of 17% observed in that study was probably underestimated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously reported 17% of grade 2-4 aGVHD following CSA/MP/MTX (CY on day þ 1) prophylaxis in class 3 adult and pediatric patients. 3 However, it should be acknowledged that most patients in that study had early graft failure (up to 30%) and a competing risk analysis was not performed to calculate the cumulative incidence of aGVHD. Therefore, the cumulative incidence of 17% observed in that study was probably underestimated.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, acute grade 2-4 GVHD still occurs in 17-55% of BMT patients who receive transplants for thalassemia from HLA-matched related donors and CSA/ MTX for GVHD prophylaxis. [3][4][5] Among many patient and disease-specific factors associated with an increased incidence of aGVHD, 3,6,7 the number of total cells or the doses of different cellular subpopulations within the graft are the most important factors for clinical outcomes such as survival or GVHD. 2,8,9 Few studies have examined the impact of T cells in the donor marrow on aGVHD after HLA-identical sibling BMT with controversial results.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also addressed the impact of risk factors on post-BMT complications. [6][7][8][9][10] During the past decades we have improved our ability to prevent and/or treat such complications, and transplantrelated mortality (TRM) has been considerably reduced 11 and delayed: in our HLA-identical sibling program TRM was 39% before 1990 (385 patients) and occurred at a median interval of 48 days from BMT (range 1-1230); TRM is currently 17% (333 patients) with a median interval from transplant of 103 days (range 8-1419) (P Ͻ 0.00001) (unpublished). Very few patients die before day +7: the 10th percentile is currently day 30, and the 75th percentile is day 202.…”
mentioning
confidence: 99%
“…It has been shown that cyclosporine plus methotrexate are superior to cyclosporine or methotrexate alone, and cyclosporine plus methotrexate plus steroids are superior to cyclosporine plus methotrexate. 4,87,88 Long-term cyclosporine extended up to 12 months after BMT may decrease the incidence of cGVHD. 4,89 In vivo ablation of alloreactive donor T cells after allogeneic hematopoietic transplantation could significantly contribute to preventing and treating GVHD.…”
Section: Prevention Of Chronic Graft-versus-host Diseasementioning
confidence: 99%
“…4,9 It has been suggested that four features of cGVHD at presentation predict poor outcome: progressive presentation of disease, concomitant thrombocytopenia, lichenoid skin or mucose-membrane histology and liver dysfunction. 10,11 Despite the improved survival in patients with established cGVHD due to the conventional, new approved and investigational therapies, many patients continue to have poor clinical function.…”
mentioning
confidence: 99%